IJCM_315A: Pesticide exposure and Diabetes Mellitus - A Community based Analytical Cross-sectionalstudy among agricultural workers in Madurai east community block, Tamil Nadu - Thendralan V; Priya S. (Wolters Kluwer Medknow Publications, 2024)
Background: World Health Organization (WHO) states that diabetes mellitus (DM) is the ninth leading cause of death in 2019¹. The study by Velmurugan et.al² in 2021 in rural Tamil Nadu shows a high prevalence of DM among agricultural workers (15.0%) compared to non-farming communities (8.7%). Pesticides, a source of Endocrine Disrupting Chemicals (EDCs) play a major etiological role in Diabetes Mellitus among them. Hence the need for present study. Objectives: 1. To estimate the prevalence of diabetes mellitus among agricultural workers in Madurai East Block 2. To find the association between pesticide exposure and other variables with DM. Methodology: A community-based cross-sectional study was conducted among 150 agricultural workers in Madurai East using multistage cluster sampling during august to November 2023.Sample size was calculated using Velmurugan et.al studyÂ². After obtaining informed consent, study population was interviewed using semi-structured validated (containing details about sociodemographics, pesticide exposure questionnaire, diabetic status) followed by anthropometric measurements in the previous day evening and advised 8 hrs fasting that night. Next day morning by 6 am, second visit was made to check fasting capillary blood glucose (CBG) using Accu-Chek glucometer. Data was analyzed using SPSS software version 21.0. Results: The mean age of the study population was 50.63 ± 13.36 years. Females constituted 66% (n=99). The mean years of agricultural work was 26.55 ± 13 years. The overall prevalence of DM among study population was 29.3%. The prevalence was slightly higher in pesticide applicators (33.33%) than agricultural workers (29.1%). Except for age, the chi-square test showed no significant association between pesticide exposure, gender, family history of DM, with DM. Conclusion: Higher Diabetic prevalence among agricultural workers demands further research to prove the hypothesis of pesticide exposure and development of diabetes.